Furthering Judicial Education : Proceedings of the Conference of Judicial Schools in Latin America - Malik, Waleed Haider; Larios Ochaita, Carlos Esteban (Washington, DC: World Bank, 2013)
The conference meeting was organized by the Supreme Court of Justice of Guatemala, in partnership with the World Bank, where judicial school directors, judges, practitioners, law students, and officials from different countries participated. The meeting aimed to harness good practices, and knowledge for furthering judicial education, based on the premise that the knowledge, and skills of judges, of court staff, and of other justice sector professionals, and users, impact significantly on the performance of the judicial system. Discussions centered around different themes, that included concepts of judicial excellence, judicial ethics, and the role of human rights, e-learning, and distance education, in-service training and evaluation methodologies, attitudinal change in the courts, and the role of education and strategies to inspire future generations of law students, and professionals. The report comprises various facets of judicial education, its challenges, and opportunities.